2004
DOI: 10.1111/j.1600-0897.2004.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Interleukin‐8 in Cervical Mucus as an Indicator for Treatment to Prevent Premature Birth and Preterm, Pre‐labor Rupture of Membranes: a Prospective Study

Abstract: Successful treatment for women with IL-8 elevations in cervical mucus decreased rates of premature birth or pPROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 22 publications
0
39
1
Order By: Relevance
“…15 The concentration of IL-8 used here was relevant physiologically and in the range that was reported recently in vivo in cervical mucus. 16 We previously showed that distension causes an increase in the expression of both PBEF and IL-8 and that PBEF is able to induce the transcription of IL-8. 5 Thus, although PBEF has no effect on chemotaxis, its induction of IL-8 would cause this.…”
Section: Commentmentioning
confidence: 95%
“…15 The concentration of IL-8 used here was relevant physiologically and in the range that was reported recently in vivo in cervical mucus. 16 We previously showed that distension causes an increase in the expression of both PBEF and IL-8 and that PBEF is able to induce the transcription of IL-8. 5 Thus, although PBEF has no effect on chemotaxis, its induction of IL-8 would cause this.…”
Section: Commentmentioning
confidence: 95%
“…The search for markers of preterm labour has identified increased expression of CXCL8 in cervical mucus, and CCL2 and MIF in maternal serum or amniotic fluid. [120][121][122] The presence of CCL8, CCL5, CCL20, CXCL5 and CCL7 in amniotic fluid is associated with microbial invasion and amniotic cavity inflammation during preterm labour. [123][124][125][126] CXCL11 level is increased in amniotic fluid during second trimester in women who subsequently developed preterm labour.…”
Section: Involvement Of Chemokines In Pregnancy Complicationsmentioning
confidence: 99%
“…219,240,242 Appendix 5, Table 94 summarises each study's salient features, stratified according to the population of women tested, i.e. asymptomatic antenatal women (two studies) 243,244 and women with symptoms of threatened preterm labour (three studies). 223,232,233 One of the included studies, on the asymptomatic antenatal population, had the test performed two-weekly between 24 and 28 weeks' gestation.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…223,232,233 One of the included studies, on the asymptomatic antenatal population, had the test performed two-weekly between 24 and 28 weeks' gestation. 244 Except for one study, 223 the studies evaluated IL-8 in cervicovaginal specimens.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%